Gasdermine E-Dependent Mitochondrial Pyroptotic Pathway in Dermatomyositis: A Possible Mechanism of Perifascicular Atrophy. Issue 5 (17th March 2020) - Liu, Meirong; Li, Ling; Dai, Tingjun; Hou, Ying; Li, Wei; Zhao, Yuying; Fang, Qi; Yan, Chuanzhu
Abstract: Different mechanisms have been proposed to explain the pathological basis of perifascicular atrophy (PFA), a pathognomonic histologic feature of dermatomyositis (DM); however, the detailed mechanisms remain to be elucidated. There is mitochondrial dysfunction in PFA and expression of mitochondrial apoptosis molecules has been reported in DM. Overexpression of gasdermin E (GSDME) can turn mitochondrial apoptosis to mitochondrial pyroptosis, a newly characterized form of programmed cell death. We determined the expression of proteins involved in the caspase-3- and GSDME-dependent mitochondrial pyroptotic pathway, including BAX, BAK, cytochrome C, caspase-9, caspase-3, GSDME, and IL-1α, in biopsied muscles from DM and control patients. Immunohistochemical analysis showed that those markers were expressed in most fibers in PFA in DM. GSDME-positive and IL-1α-positive staining was mainly localized around punched-out vacuoles or sarcolemma. These markers were significantly upregulated at the protein and mRNA levels in DM versus controls. Our results suggest that caspase-3- and GSDME-dependent mitochondrial pyroptosis are involved in the pathogenetic mechanisms of PFA in DM and that targeting GSDME-dependent mitochondrial pyroptosis may be an effective therapeutic approach for this condition.